Simulation of the Electrostatic Distribution in the Proximity Focusing Structure of an EBCMOS - Wei Wang; Ye Li; Weijun Chen; De Song; Xin Wang (IEEE Photonics Journal)
The electrostatic distribution of an electron bombarded CMOS (EBCMOS) was simulated by Ansoft Maxwell 3D software. Specifically, we studied how the electrostatic distribution was affected by the structure of a back-side bombarded CMOS (BSB-CMOS) and the anode position in electron-bombarded sensors. The simulation results reveal that the electrostatic field may cause a fault in the signal readout of the BSB-CMOS when the anode is positioned under the BSB-CMOS. In contrast, we found that the structure of an EBCMOS will aid electron focusing when the anode is positioned above the BSB-CMOS and the doping concentration of the electron multiplier layer is high. However, the high doping concentration of the electron multiplier layer will reduce the electron collection efficiency due to its rapid electron-hole recombination. We then designed a structure in which the multiplier layer has an overlying ultra-thin highly-doped layer, with an electrostatic distribution that functions to focus electrons. At the same time, this configuration can effectively prevent most of the multiplier electrons from recombining because ultra-thin highly-doped layer is much thinner than incident depth for the high-energy electron. This simulation study will provide a theoretical foundation for the fabrication of high-performance EBCMOS devices. Graphic abstract: a) EBCMOS physical model in Ansoft Maxwell 3D; b) The distribution of electrostatic distribution for BSB-CMOS with an ultra-thin heavily-doped layer. Electrostatic distribution of EBCMOS with different configurations were simulated. The results reveal that the electrostatic field may cause an erroneous readout of the BSB-CMOS if the anode is positioned under the BSB-CMOS. If the high voltage anode is positioned above the CMOS sensor, this is improved, especially when an ultrathin highly-doped multiplier layer is added to improve electron collection efficiency. This study provides a theoretical foundation for the fabrication of high performance EBCMOS devices.